The role of pH in heavy metal contamination of urban soil - Kazlauskaitė-Jadzevičė, Asta; Volungevičius, Jonas; Gregorauskienė, Virginija; Marcinkonis, Saulius (Journal of Environmental Engineering and Landscape Management, 2014)
The aim of this study to assess interdependence between urban soil pH and its accumulation of heavy metals. The article meant to be a contribution to a better knowledge of peculiarities and diagnostics of urban soil and its anthropogenic transformation. The hypothesis assumes that relationship between urban soil pH and its accumulation of heavy metals may be determined by the origin and age of parent material as well as the nature and degree of the anthropogenic impact. The spatial variability of topsoil pH level was performed in 100 points in eldership of Šnipiškės of the city Vilnius. Laboratory analysis was based on ISO 10390:2005. Samples were collected from 20 cm topsoil layer in the same sampling points where have been analysed concentrations of topsoil chemical elements using optical atomic emission spectrophotometry. The contamination of urban soils exhibits somewhat different compared to agricultural soils. In contradiction to earlier studies in Lithuanian agricultural soils where strong correlation between soil pH and Cr, Cd, Pb, Ni, Cu and Zd found, the conducted analysis shows a statistically reliable, but very weak (